Формування художньо-педагогічної освіти в історичному дискурсі - Каленюк, Ольга Миколаївна; Kaleniuk, Olha M. (Мистецький інститут художнього моделювання та одягу імені Сальвадора Далі, 2015)
У статті проведено аналіз художньо-педагогічної освіти періоду ХVІІ-ХХІ століття. Проаналізовано ефективність академічної системи освіти та її реформування на підґрунті концептуальних ідей учених епохи Просвітництва. Розглянуто дидактичні та теоретичні методи формування фахових знань художника-педагога. Здійснено намір осмислення періодизації художньо-педагогічної освіти. Окреслено домінуючі методологічні підходи у викладанні фахових предметів у сучасній освіті. Визначено пріоритетні напрями у формуванні фахових знань майбутнього митця.

Analysis of the artistic and pedagogical education of the period of ХVІІ-ХХІ century was researched in the article. Efficiency of the academic education system and its reformation on ideas of the age of Enlightenment was analyzed. Training features of art teachers in Europe and the creation of a national educational system and the preparation of national teacher staff in Ukraine were defined. Didactic and theoretical methods of professional knowledge formation of an artist-teacher are considered. Intention of periodization understanding of artistic and pedagogical education was implemented. The dominating methodological approaches in teaching of professional subjects in modern education were outlined. Priority areas in professional knowledge formation of future artist were determined.
Formation of artistic and pedagogical education in historical discourse
Keywords: академізм; academism; художньо-педагогічна освіта; artistic and pedagogical education; художник-педагог; artist-teacher; методологічні підходи; methodological approaches